2017
DOI: 10.1111/bjh.14842
|View full text |Cite
|
Sign up to set email alerts
|

Roles of APOL1 G1 and G2 variants in sickle cell disease patients: kidney is the main target

Abstract: In African-American patients with sickle cell disease (SCD), APOL1 G1 and G2 variants are associated with increased risk of sickle cell nephropathy (SCN). To determine the role of APOL1 variants in SCD patients living in Europe, we genotyped 152 SCD patients [aged 30·4 (24·3-36·4) years], mainly of Sub-Saharan African ancestry, for APOL1 G1 and G2 and for variants of four genes with kidney tropism (GSTM1, GSTT1, GSTP1, and HMOX1). Homozygous or double-heterozygous APOL G1 and G2 genotypes were strongly associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 56 publications
0
47
1
Order By: Relevance
“…Finally, the current study did not evaluate genetic variants associated with development of albuminuria including APOL1. Future research should consider screening for these genetic variants associated with albuminuria in their trial design and evaluate the impact of sickle cell modifying therapies or renoprotective agents on preventing albuminuria in children with these high‐risk genetic variants …”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current study did not evaluate genetic variants associated with development of albuminuria including APOL1. Future research should consider screening for these genetic variants associated with albuminuria in their trial design and evaluate the impact of sickle cell modifying therapies or renoprotective agents on preventing albuminuria in children with these high‐risk genetic variants …”
Section: Discussionmentioning
confidence: 99%
“…Puerto Rico outperforms the US states and the District of Columbia ("states" hereafter) on some measures of coverage and access, 3 but substantial problems with quality of care have been documented. 4 Compared with Hispanics in the states, Hispanics in Puerto Rico receive lower quality care for chronic conditions; have worse control of diabetes, hyperlipidemia, and hypertension; and use effective medications for rheumatoid arthritis and chronic obstructive pulmonary disease less frequently. 5 In this study, we compared 1-year mortality rates and predialysis nephrology care among Hispanics in Puerto Rico and Hispanics and whites in the states who initiated maintenance hemodialysis or peritoneal dialysis between 2006 and 2015.…”
Section: Trends In Mortality Among Patients Initiating Maintenance DImentioning
confidence: 99%
“…1 Age of KRT onset is typically younger for individuals with 2 versus 0 to 1 RRVs. [2][3][4][5] It is likely that the relationship between high-risk genotype and risk of KRT attenuates with aging, but it is unclear whether there is an age threshold when APOL1 may no longer be a strong risk factor for KRT. We performed a retrospective analysis of AASK 1,6,7 to examine whether there is an age threshold when the effect of APOL1 genotype on KRT risk attenuates among blacks with baseline CKD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The longer HMOX1 GT-tandem repeat polymorphism in the UIC cohort was associated with lower eGFR [69]. Another smaller study of 152 SCD patients in Europe failed to delineate a relationship between the HMOX1 rs743811 variant and kidney disease [70]. However, another study of young SCD patients (median age 15 years) from Cameroon demonstrated a trend to association between HMOX1 rs743811 and macroalbuminuria, although this did not quite reach statistical significance ( p = 0.06) [62].…”
Section: Modifying Factorsmentioning
confidence: 99%